A Systematic Review Comparing Dose Response of Exercise on Cardiovascular and All-Cause Mortality. Issue 4 (November 2019) - Moxley, Elizabeth; Habtzghi, Desale
It is well established that exercise improves cardiovascular and all-cause mortality, although an ideal dose of exercise is not known. The physical activity guidelines currently recommend 150 minutes per week of moderate-intensity exercise or 75 minutes of vigorous-intensity activity. Most individuals do not engage in adequate exercise, although a safe upper limit does not exist and a too much exercise hypothesis has recently emerged. This review of the literature analyzes studies that have evaluated exercise dose response on all-cause and cardiovascular mortality for the purpose of determining safe and effective exercise prescriptions. Searches were performed in PubMed and CINAHL between 2010 and 2018 to identify six studies that met inclusion criteria. Moderate-intensity exercise reduced all-cause mortality in five of six studies, whereas low-dose exercise most effectively improved all-cause mortality in three studies, and cardiovascular mortality in one study. Vigorous-intensity exercise or extreme doses demonstrated variable outcomes and remain controversial; two studies found vigorous-intensity exercise beneficial to improve health, two studies discouraged vigorous exercise, and two studies had less conclusive outcomes. It is not surprising that any amount of exercise improves health compared with none at all, with the greatest benefits observed when sedentary individuals began exercising. Low-dose exercise should be recommended to everyone with a goal of meeting the minimal requirements according to guidelines for decreased all-cause and cardiovascular mortality. Additional research to more thoroughly understand exercise dose response and motivate individuals to improve exercise engagement is currently warranted.